Vocabulary and Reading Performances of Redesignated Fluent English Proficient Students. Issue 4 (30th November 2016) - Hwang, Jin Kyoung; Lawrence, Joshua Fahey; Collins, Penelope; Snow, Catherine
Abstract : In this article, the researchers examined general vocabulary, academic vocabulary, and reading comprehension growth trajectories of adolescent redesignated fluent English proficient (RFEP) students using individual growth modeling analysis. The sample included 1, 226 sixth‐ to eighth‐grade RFEP students from six middle schools in an urban school district in California. Students completed up to four waves of reading‐related measures during a 2‐year time period. Findings indicate that (a) students' scores on vocabulary and reading assessments were positively correlated with their years since redesignation and (b) students on average showed growth over time on all outcomes and the rate of growth did not differ by their years since redesignation. The results suggest that recently redesignated students may need sustained support to ensure continued progress in their English language development.